The study of expatriates ‘motivation towards job performance in semiconductor industry in Melaka based on McClelland’s theory of needs / Abdul Razak Abdul Mutalib - Abdul Mutalib, Abdul Razak (Faculty of Business and Management, 2015)
This research was conducted for the purpose of “Motivation as Expatriates in Semiconductor Industry in Melaka based on McClelland’s Theory of Needs”. The main objective of this research was to identify the relationship of McClelland’s Theory of Needs towards expatriates. It is part of researcher’s intention to provide a few suggestions for expatriates on how the McClelland’s Theory of Needs would impact their motivation as expatriates in host-country.